No bater da palma, o "lundu" se torna "dança" - a "dança" que me torna "professor(a)" - PANTOJA, Antonio Benedito Lima (2024)
This "Course Completion Work - TCC", entitled: "In the clap of the palm, the "Lundu" becomes "Dance" - The "Dance" that makes me "Teacher". The research problem was: " Know the importance of knowing the origin and history of "Lundu Marajoara" related to the dance teacher training process and its contributions to the culture of "Soure and the Amazon". For the development of its research methodology, the main theoretical contribution was the concept of "cultural memory" in order to support a conception of the type of research based on the idea of "body-archive". The work was organized into three chapters: Chapter 1 - THE CONSTRUCTION OF THE FRIENDSHIP TIES THAT LED ME TO DANCE; Chapter 2 - ARRIVAL AT CRUZEIRINHO AND THE MEETING WITH MARAJOARA; Chapter 3 - THIRD THE EXPERIENCE AND PRACTICE IN LUND MARAJOARA DANCE AND ITS CONTRIBUTIONS TO MY TRAINING AS A DANCE TEACHER. The study aims to bring contributions to the citizens of the municipality of "Soure" by providing self-recognition regarding its cultural richness and its history as a society that is important not only for the residents of the municipality of "Soure" but also for history and culture of Marajó and the Amazon.